A prática do registro da rotina de uma turma de Educação Infantil e os sentidos e significados atribuídos pelas crianças e sua professora - Juliana Basilio Medrado (2014)
The aim of this study was to comprehend how children between four and five years old developed meanings for school-related school practices proposed by either the school or the teacher. The data for this research were collected from an elementary class in a private school in Belo Horizonte, MG, Brazil, in the first semester of 2012. In this context, we tried to comprehend the strategies used by these children to re-create and appropriate such practices, by providing them with meaning. In order to do so, we were supported by the concepts of formal education, childhood, child, school practices and meaning, based on the theoretical references that constitute the Social Historical Theory from Vigotski (1934/1993; 1931/1995; 2001/2004; 1984/2007; 1984/2010; 2001)and the Sociology of Childhood from Corsaro (1985; 2005/2011; 2009) and Sarmento (1997; 2003; 2008). This is a qualitative research aimed at analyzing the relations that children establish with a particular school practice. We chose the construction of routine register as the school practice to evaluate how children relate to and engage with it and what meanings they attribute to it. In this sense, we adopted the following instruments of research: participative observations followed by annotation on a field notebook; analysis of video recordings; and interviews/conversations with teachers and children. Children participated in the research as study subjects that were also involved in our analysis process. As a result, we learned that the teachers attitudes of stimulating the autonomy of the students and establishing frequent dialogs to consider their demands allowed the children to appropriate those possibilities and become actively involved in those school practices, attributing several meanings to them according to their life experience and to their conception of the world. In the case of the practice of routine register, the children searched for diverse meanings for the actions related to the construction and register of the routine. Through their speech and actions, we could observe their movement in order to be able to appropriate the social function of this practice, which included: organizing the time and space experienced by the group by planning activities; constructing a memory of the day, reminding them of what happened; learning how to write the numbers and to draw, without disregarding writing as a support for exercising this practice.